EFFECT OF GIVING HERBAL SOLUTION IN DRINKING WATER ON FINAL BODY WEIGHT, FEED EFFICIENCY AND INCOME OVER FEED COST OF SUPER NATIVE CHICKEN - F., SUKMARIYADI; TANWIRIAH, W.; GARNIDA, D. (Majalah Ilmiah Peternakan; Vol 26 No 3 (2023): Vol. 26 No. 3 (2023)DO - 10.24843/MIP.2023.v26.i03.p03, 2024)
This research aims to determine the effect and dosage of giving herbal solutions in drinking water on final weight, feed efficiency and Income Over Feed Cost (IOFC) Super Native Chicken. With a ratio of ginger, turmeric, garlic and water, namely 1:1:1:1. This research was carried out for 8 weeks starting in June 2023. There were 100 Super Native Chickens. The research was carried out experimentally with a Completely Randomized Design (CRD) with 4 treatments and 5 replications so that there were 20 experimental units. The experimental treatments were P0 (water without GTG solution), P1 (water + 0.5% GTG solution), P2 (water + 1.0% GTG solution), and P3 (water + 1.5 GTG solution %). The data obtained was then analyzed using ANOVA to determine the effect of treatment, then Duncan’s further test was carried out to determine the differences between the treatments tested. The parameters observed were final weight, feed efficiency, and income over feed cost. The research results showed that giving her- bal solutions in the drinking water of Super Native Chicken had an effect on final weight, feed efficiency and Income Over Feed Cost. Providing 1% of the GTG herbal solution in drinking water provides the best results in final weight, feed efficiency and Income Over Feed Cost for Super Native Chicken.